Enduring Encounters: Maps of Japan from Leiden University Library - Leca, Radu; Storms, Martijn (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
While Asian and Western cartographies are often considered separate traditions, maps of Japan kept in Leiden University Libraries often show a commonality of method and purpose. Despite the expulsion of Phillip Franz von Siebold from Japan in 1829, the norm was for friendly exchanges of scientific knowledge. One of the highlights of this volume are annotated drafts and proofs of Siebold's map of Japan, published and discussed for the first time alongside Japanese source maps. Five essays by worldwide experts in the history of cartography and of Dutch-Japanese relations accompany extensive catalogue entries for over fifty maps. Contributors are: Aoyama Hiro'o, Edward Boyle, Radu Leca, Martijn Storms, and Uesugi Kazuhiro.